Wear-resistant, waterproof and antiskid round floating point rubber coiled material

Through multi-layer structural design and nano-silica coating, the problem of degradation in circular floating point rubber coils in high temperature or humid environments is solved, and high-performance applications are achieved under different environmental conditions.

CN119859478APending Publication Date: 2025-04-22JIANGSU JIAFU NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510185237.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

When used in high temperature or humid environments, it is difficult to maintain wear resistance, waterproofness and anti-slip properties.

Method used

It adopts a multi-layer structural design, including a wear-resistant and anti-slip surface, an intermediate functional layer and a base bonding layer, and is coated with a nano-silicon dioxide coating on the circular floating point surface. The intermediate functional layer consists of a enhanced physical performance layer, a buffer performance layer and a waterproof reinforcement layer.

Benefits of technology

Maintaining the wear resistance, waterproofness and anti-slip properties of the coil in high temperature or humid environments broadens the application range of the coil and improves the overall stability and flame retardant performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859478A_ABST
    Figure CN119859478A_ABST
Patent Text Reader

Abstract

The invention discloses a wear-resistant, waterproof and antiskid round floating point rubber coiled material, and relates to the technical field of rubber waterproof coiled materials, the wear-resistant, waterproof and antiskid round floating point rubber coiled material comprises a wear-resistant and antiskid surface layer, a middle functional layer is attached to the bottom of the wear-resistant and antiskid surface layer, a base layer bonding layer is attached to the bottom of the middle functional layer, and round floating points are uniformly arranged on the top of the wear-resistant and antiskid surface layer. The top of the round floating points and the top of the wear-resistant anti-skid surface layer are coated with a 0.5 mm nano-silica coating. A multi-layer structure is adopted to effectively prevent water from permeating, the multi-layer structure comprises the base layer bonding layer in direct contact with the base layer ground, the middle functional layer playing a role in connecting the top and the bottom and the outermost wear-resistant anti-skid surface layer in direct contact with the outside, and the advantages of various rubber materials are integrated; and the surfaces of the round floating points are coated with a layer of nano silicon dioxide, so that a microscopic hydrophobic structure is formed on the surfaces of the round floating points, and the coiled material can still keep the original wear resistance, water resistance and skid resistance when used in a high-temperature or humid environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber waterproof coiled materials, in particular to a wear-resistant, waterproof and anti-skid round floating point rubber coiled material. Background Art

[0002] Round floating point rubber roll is a roll material made of rubber as the main raw material, with round floating points on the surface. It is widely used in commercial places, industrial places, sports places, medical places, educational places and home places. The existing round floating point rubber waterproof roll is difficult to maintain its original wear resistance, waterproofness and anti-slip properties when used in high temperature or humid environment.

[0003] The defects of existing round floating point rubber coils are: 1. Patent document CN219621120U discloses a rubber composite self-adhesive waterproofing membrane, which mainly considers how to improve the overall wear resistance of the membrane and increase the service life of the composite waterproofing membrane, but does not consider how to make the membrane still maintain its original wear resistance, waterproofness and anti-slip performance when used in a high temperature or humid environment; 2. Patent document CN214194007U discloses a polymer rubber sports coil, which mainly considers how to extend the overall service life and increase the overall waterproofness, thereby ensuring the overall use strength and better durability. It does not consider how to make the wear-resistant and anti-skid layer directly in contact with the outside world be used in different climatic conditions and chemical environments to broaden the application range of the coil; 3. Existing round floating point rubber coils will delaminate after long-term use, making it difficult to ensure the overall stability of the coils; 4. It is difficult for existing round floating point rubber coils to have good wear resistance, anti-aging performance and flame retardant properties at the same time. Summary of the invention

[0004] The object of the present invention is to provide a wear-resistant, waterproof and anti-skid round floating point rubber coiled material to solve the problems raised in the above background technology.

[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: a wear-resistant, waterproof and non-slip round floating point rubber coil, comprising a wear-resistant and non-slip surface layer, the bottom of the wear-resistant and non-slip surface layer is bonded to an intermediate functional layer, the bottom of the intermediate functional layer is bonded to a base bonding layer, the top of the wear-resistant and non-slip surface layer is evenly arranged with round floating points, the round floating points and the top of the wear-resistant and non-slip surface layer are coated with a 0.5 mm nano-silicon dioxide coating, the intermediate functional layer comprises an enhanced physical property layer, a buffering property layer and a waterproof reinforcement layer, the bottom of the waterproof reinforcement layer is bonded to the top of the base bonding layer, the buffering property layer is located between the waterproof reinforcement layer and the enhanced physical property layer, and the top of the enhanced physical property layer is bonded to the bottom of the wear-resistant and non-slip surface layer.

[0006] Preferably, the raw materials include the following components: natural rubber, silicone rubber, chloroprene rubber, styrene-butadiene rubber, filler, vulcanizer, accelerator, softener, antioxidant, flame retardant, polyester fiber, polyurethane foam, stabilizer, talcum powder, curing agent and diluent; The preparation method of the round floating point rubber coil comprises the following steps: Step S1: Raw material preparation and pretreatment: pretreating the natural rubber, silicone rubber and chloroprene rubber respectively; Step S2: firstly, preparing a wear-resistant and anti-skid surface layer, putting the natural rubber, silicone rubber and chloroprene rubber pretreated in step S1 into an internal mixer and mixing them, and preparing a wear-resistant and anti-skid surface layer with a thickness of 1.5 mm through an extrusion molding process; Step S3: Preparation of intermediate functional layer: preparing an enhanced physical performance layer, a buffer performance layer and a waterproof reinforcement layer, and firmly combining the three-layer structure by a bonding process to form a 2 mm intermediate functional layer; Step S4: Mix the polyurethane adhesive, curing agent and diluent in proportion, and stir at a speed of 240-280 rpm for 10-20 minutes at room temperature to prepare an adhesive, and then use a roller coater to evenly apply the adhesive on one side of the intermediate functional layer to form a 1 mm thick base bonding layer, and cover the other side of the base bonding layer with a layer of release paper, wherein the mass ratio of the polyurethane adhesive, the curing agent and the diluent is 10:0.1-0.3:1-3; Step S5: Laminating and post-processing: Laminating the semi-finished product made in step S4 with the wear-resistant and anti-skid layer to form a completed round floating point rubber coil, and vulcanizing the coil as a whole; Step S6: Quality monitoring and packaging: The physical properties of the manufactured coils are tested according to GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber" standard, and the flame retardant properties of the coils are tested according to GB10707-1989 "Rubber combustion performance determination oxygen index method".

[0007] Preferably, in step S2, the following steps are also included: Step S21: putting the pretreated natural rubber, silicone rubber, chloroprene rubber, filler, vulcanizer, accelerator, antioxidant and softener into an internal mixer according to a certain proportion, with the internal mixing temperature being 90° C. to 110° C., the rotor speed being 50 to 70 rpm, and the mixing time being 5 to 10 min to obtain a mixed rubber; Step S22: Extruding the rubber mixture with an extruder, and passing the rubber mixture through a die with a round floating point shape to form a rubber sheet with round floating points, the temperature of the extruder is 80° C. to 90° C., and the screw speed is 10 to 30 rpm; Step S23: placing the formed rubber sheet with round floating points into a vulcanizing tank for vulcanization at a temperature of 150° C. to 170° C. for 10 to 20 minutes; Step S24: coating a layer of nano-silicon dioxide on the side with the round floating points, and drying at a temperature of 40-60° C. for 10-40 minutes to form a nano-silicon dioxide coating.

[0008] Preferably, in step S1, the following steps are also included: Step S11: natural rubber pretreatment: natural rubber is put into an open mill, and nano calcium carbonate is added thereto, and the roller distance is adjusted to 1 mm, and the roller speed is 10-20 rpm for plastication for 5-8 minutes to obtain modified natural rubber; Step S12: silicone rubber pretreatment: firstly, the silicone rubber is placed in a plasma treatment device using plasma treatment technology, and activated for 2-3 minutes in an argon plasma atmosphere, and then the activated silicone rubber, AGE and chloroplatinic acid are placed in a reactor for a silylation reaction, so that the grafted monomer is grafted onto the silicone rubber molecular chain, wherein the temperature of the reactor is 85°C to 95°C, and the reaction time is 5 hours. After the reaction is completed, xylene is used for extraction to remove unreacted grafted monomer and catalyst, and the extracted silicone rubber is dried in a vacuum drying oven at a temperature of 85°C for 4.5 hours. Then, the grafted modified silicone rubber, flame retardant and zinc oxide are placed in an internal mixer at a temperature of 85°C to 95°C, a rotor speed of 40 to 60 rpm, and a mixing time of 5 to 10 minutes to obtain modified silicone rubber; Step S13: pretreatment of chloroprene rubber: put the chloroprene rubber into an internal mixer for preliminary mixing, the temperature of the internal mixer is 80°C to 85°C, the rotor speed is 30 to 50 rpm, after 4 to 6 minutes, add magnesium hydroxide and triphenyl phosphate, adjust the temperature to 90°C to 95°C, the rotor speed is 40 to 60 rpm, mix for 6 to 10 minutes, and obtain modified chloroprene rubber.

[0009] Preferably, in step 3, the following steps are also included: Step S31: putting the pretreated natural rubber and styrene-butadiene rubber into an internal mixer for preliminary mixing, the mixing temperature is 70°C-90°C, the rotor speed is 30-40rpm, and the mixing time is 5-10min, then firstly wrapping the rubber after preliminary mixing with a roller, and then adding polyester fiber to the rubber, wherein the temperature is 90°C, the rotor speed is 50-55rpm, and the mixing time is 8-9min, then adding a vulcanizing agent and an accelerator, and continuing to mix at 90°C and 50-55rpm for 3-5min, then putting the mixed material into a vulcanizing device, vulcanizing at 120-130°C for 25-30min, and extruding with an extruder to obtain an enhanced physical property layer, wherein the extruder temperature is 160-170°C; Step S32: putting the pretreated chloroprene rubber and a small piece of polyurethane foam into an internal mixer, rotating at a temperature of 80-85° C. and a speed of 40-45 rpm, mixing for 5-8 minutes, then adding a vulcanizing agent, an accelerator and an antioxidant, continuing to internally mix at 80-85° C. and a speed of 40-45 rpm for 3-5 minutes, and extruding with an extruder to obtain a buffer performance layer, wherein the extruder temperature is 170° C.; Step S33: preheating the asphalt to 165°C in a high-speed mixer, adding SBS modifier after melting it, stirring at a speed of 1200-1400rpm, adding talcum powder, antioxidant and stabilizer to the mixed system after 40min, and continuing to stir at a speed of 1200-1400rpm for 40min, wherein the temperature is maintained at 170°C, and forming a waterproof reinforcement layer through an extruder with the mixed material, wherein the extruder temperature is 175°C; Step S34: first apply rubber adhesive to one side of the enhanced physical performance layer made in step S31, then fit the buffering performance layer made in step S32 thereon, and use a platen press to apply pressure of 0.5-1MPa, then apply rubber adhesive to the other side of the buffering performance layer, fit the waterproof reinforcement layer made in step S33 thereon, and also use a flat plate press to apply pressure of 1-2MPa. After fitting, cure at room temperature for 24-48h to form a 2mm intermediate functional layer.

[0010] Preferably, in step S5, the following steps are also included: Step S51: Laminating process: Apply adhesive to the other side of the middle functional layer, and then laminate the side of the wear-resistant and anti-skid layer without the round floating point to it, and compact it with a flat press at a pressure of 1-2MPa. After laminating, let it stand at room temperature for 24-48 hours to obtain a completed round floating point rubber coil; Step S52: Overall vulcanization: Use a vulcanization tank to vulcanize the laminated coils, wherein the vulcanization temperature is 145-155° C. and the vulcanization time is 10-30 minutes.

[0011] Preferably, in step S21, the mass ratio of natural rubber, silicone rubber, chloroprene rubber, filler, vulcanizer, accelerator, antioxidant and softener is 15-25:10-13:9:5-10:0.5-1.5:0.1-0.5:0.3:0.1.

[0012] Preferably, in step S11, the mass ratio of natural rubber to nano-calcium carbonate is 10:0.1-0.5, and in step S13, the mass ratio of chloroprene rubber, magnesium hydroxide and triphenyl phosphate is 10:0.1-0.5:0.2.

[0013] Preferably, in step S31, the mass ratio of natural rubber, styrene-butadiene rubber and polyester fiber, vulcanizer and accelerator is 7:3-4:0.5-1:0.1:0.2, in step S32, the mass ratio of chloroprene rubber, polyurethane foam, vulcanizer, accelerator and antioxidant is 10:2-4:0.1-0.2:0.1:0.1, and in step S33, the mass ratio of asphalt, SBS modifier, talcum powder, antioxidant and stabilizer is 10-15:0.3-1:0.1-0.5:0.1:0.1.

[0014] Preferably, the flame retardant in step S12 is a mixture of ammonium polyphosphate and melamine.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The multi-layer structure of the present invention can effectively prevent the penetration of water. The multi-layer structure includes a base bonding layer directly in contact with the base ground, an intermediate functional layer that plays a connecting role, and an outermost wear-resistant and anti-skid surface layer that directly contacts the outside world. The intermediate functional layer is composed of a waterproof reinforcement layer, a buffer performance layer, and an enhanced physical performance layer to ensure that the waterproof reinforcement layer is well bonded to the other layers to avoid gaps that lead to water leakage. Each layer is prepared from a composite rubber material, which combines the advantages of various rubber materials. A layer of nano-silicon dioxide is coated on the surface of the circular floating point to form a microscopic hydrophobic structure on the surface of the circular floating point. Even in a wet state, a high friction coefficient can be maintained, so that the coiled material can still maintain its original wear resistance, waterproofness and anti-skid properties when used in a high temperature or humid environment.

[0016] 2. The present invention adopts natural rubber, silicone rubber and chloroprene rubber to blend into the wear-resistant and anti-skid layer, which effectively combines the advantages of each, improves the wear resistance of the wear-resistant and anti-skid layer, and reduces the wear rate. Natural rubber has good elasticity and tensile strength, can provide a certain resilience when rubbed, and reduce wear. Silicone rubber has excellent high temperature resistance and chemical corrosion resistance, and can maintain good stability in complex friction environments. The wear resistance of chloroprene rubber itself is also relatively outstanding, and the chlorine atoms in its molecular structure give it certain oil resistance and solvent resistance. It performs well in friction scenarios where it may contact chemical substances, so that the wear-resistant and anti-skid layer directly in contact with the outside world can be used in different climatic conditions and chemical environments, which broadens the application range of the coiled material.

[0017] 3. The present invention performs a vulcanization treatment on the whole after laminating the layers, optimizes the cross-linking structure of the rubber by changing the vulcanization system, and adopts a high-efficiency combination of vulcanizer and accelerator to make the rubber form a more stable three-dimensional network structure after vulcanization, so as to further enhance the bonding force between the layers and ensure the overall quality of the coil.

[0018] 4. The present invention improves the performance of the rubber itself by modifying the natural rubber, silicone rubber and chloroprene rubber in the raw materials, and adopts nanomaterials to blend with natural rubber to enhance the wear resistance of the rubber, and to a certain extent, improve the anti-aging performance of the rubber, because the nanoparticles can absorb and disperse ultraviolet rays, reduce the damage of ultraviolet rays to the rubber molecular chain, and introduce grafted monomers into the silicone rubber molecular chain to improve the compatibility of the silicone rubber, so that it can be better combined with other rubbers in the subsequent blending, thereby improving the performance of the entire rubber system, and further improving the flame retardancy of silicone rubber and chloroprene rubber. When a fire occurs, on the one hand, the coil can form a stable carbon layer to prevent the spread of the flame, and on the other hand, the inorganic flame retardant therein decomposes and absorbs heat at high temperature, releases water vapor, plays a role in cooling and diluting the combustible gas, and further prevents the spread of the fire.

[0019] Figure 1 It is a schematic diagram of the three-dimensional structure of the present invention; Figure 2 It is a schematic diagram of the planar structure of the intermediate functional layer of the present invention.

[0020] In the figure: 1. Wear-resistant and anti-slip surface layer; 2. Middle functional layer; 3. Base bonding layer; 4. Round floating points; 5. Enhanced physical performance layer; 6. Buffering performance layer; 7. Waterproof reinforcement layer. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] The present invention provides a wear-resistant, waterproof and anti-skid round floating point rubber coil. Step S1: Raw material preparation and pretreatment: natural rubber is placed in an open mill, and nano-calcium carbonate is added thereto, and the roller distance is adjusted to 1 mm, and the roller speed is 15 rpm for plasticization for 6 minutes to obtain modified natural rubber. Then, plasma treatment technology is first used to place the silicone rubber in a plasma treatment device, and activation treatment is performed for 2 minutes in an argon plasma atmosphere. After that, the activated silicone rubber, AGE and chloroplatinic acid are placed in a reactor for a silylation reaction to graft the grafted monomer onto the silicone rubber molecular chain, wherein the temperature of the reactor is 90° C. and the reaction time is 5 hours. After the reaction is completed, xylene is used for extraction to remove unreacted grafted monomer and catalyst, and the extracted silicone rubber is placed in a vacuum drying oven. Drying, the temperature is 85 ° C, the drying time is 4.5h, then the grafted modified silicone rubber, flame retardant and zinc oxide are placed in an internal mixer, the temperature is 90 ° C, the rotor speed is 50rpm, the mixing time is 7min, and the modified silicone rubber is obtained. Then the chloroprene rubber is placed in the internal mixer for preliminary mixing. The temperature of the internal mixer is 80 ° C, the rotor speed is 40rpm, and magnesium hydroxide and triphenyl phosphate are added thereto after 5min. The temperature is adjusted to 95 ° C, the rotor speed is 60rpm, and mixing is carried out for 6min to obtain modified chloroprene rubber, wherein the mass ratio of natural rubber to nano-calcium carbonate is 10:0.3, and the mass ratio of chloroprene rubber, magnesium hydroxide and triphenyl phosphate is 10:0.3:0.2; Step S2: Preparation of wear-resistant and non-slip surface layer 1: The pre-treated natural rubber, silicone rubber, chloroprene rubber, filler, vulcanizer, accelerator, antioxidant and softener are put into an internal mixer according to a proportion, the internal mixing temperature is 100°C, the rotor speed is 60rpm, the mixing time is 10min, and a rubber mixture is obtained. The rubber mixture is then extruded and formed by an extruder, and the rubber mixture is passed through a die with a round floating point shape to form a rubber sheet with a round floating point 4. The temperature of the extruder is 90°C, the screw speed is 25rpm, and the obtained rubber sheet is then extruded and formed by an extruder. The rubber sheet with round floating point 4 after molding is put into a vulcanizing tank for vulcanization at a vulcanization temperature of 160° C. for 15 minutes. Finally, a layer of nano-silicon dioxide is coated on one side with round floating point 4, and dried at a temperature of 50° C. for 30 minutes to form a nano-silicon dioxide coating, wherein the mass ratio of natural rubber, silicone rubber, chloroprene rubber, filler, vulcanizing agent, accelerator, antioxidant and softener is 15-25:10-13:9:5-10:0.5-1.5:0.1-0.5:0.3:0.1; Step S3: Preparation of intermediate functional layer 2: The pretreated natural rubber and styrene-butadiene rubber are placed in an internal mixer for preliminary mixing, the mixing temperature is 80°C, the rotor speed is 30 rpm, and the mixing time is 7 min. Then, the rubber after preliminary mixing is rolled, and then the polyester fiber is added to the rubber, wherein the temperature is 90°C, the rotor speed is 50 rpm, and the mixing time is 8 min. Then, the vulcanizing agent and accelerator are added, and the mixing is continued at 90°C and 50 rpm for 4 min. Then, the mixed material is placed in a vulcanization device, vulcanized at 125°C for 25 min, and extruded. The pretreated chloroprene rubber and a small piece of polyurethane foam were put into an internal mixer, and the mixture was rotated at 40 rpm at 85°C for 6 min. The vulcanizing agent, accelerator and antioxidant were added, and the mixture was continuously mixed at 85°C and 40 rpm for 4 min. The mixture was extruded by an extruder to obtain a buffering performance layer 6, wherein the extruder temperature was 170°C. The asphalt was then placed in a high-speed mixer and preheated to 165°C. After the mixture was melted, the SBS modifier was added and the mixture was mixed at 1300 rpm. Stir at high speed for 40 minutes, add talcum powder, antioxidant and stabilizer into the mixed system, continue stirring at 1300rpm for 40 minutes, keep the temperature at 170℃, and use the mixed material to form waterproof reinforcement layer 7 through extruder, wherein the extruder temperature is 175℃, finally, apply rubber adhesive to one side of the prepared enhanced physical performance layer 5, and then fit the prepared buffer performance layer 6 thereto, and use a platen press to apply pressure of 0.7MPa, then apply rubber adhesive to the other side of the buffer performance layer 6, and fit the prepared waterproof reinforcement layer 7 thereto, and similarly adopt Apply pressure with a flat press, at this time the pressure is 1.5 MPa, after lamination, cure at room temperature for 36 hours to form a 2 mm intermediate functional layer 2, wherein the mass ratio of natural rubber, styrene-butadiene rubber and polyester fiber, vulcanizer and accelerator is 7:3-4:0.5-1:0.1:0.2, the mass ratio of chloroprene rubber, polyurethane foam, vulcanizer, accelerator and antioxidant is 10:2-4:0.1-0.2:0.1:0.1, and the mass ratio of asphalt, SBS modifier, talcum powder, antioxidant and stabilizer is 10-15:0.3-1:0.1-0.5:0.1:0.1; Step S4: The polyurethane adhesive, curing agent and diluent are mixed in proportion, and stirred at a speed of 260 rpm for 15 minutes at room temperature to prepare an adhesive, and then the adhesive is evenly applied to one side of the intermediate functional layer 2 by a roller coater to form a 1 mm thick base bonding layer 3, and a layer of release paper is covered on the other side of the base bonding layer 3, wherein the mass ratio of the polyurethane adhesive, the curing agent and the diluent is 10:0.2:1.5; Step S5: Lamination and post-processing: Apply adhesive to the other side of the intermediate functional layer 2, and then laminate the side of the wear-resistant and anti-skid layer 1 without the round floating point 4 thereto, and compact it with a flat press at a pressure of 1.5 MPa. After lamination, let it stand at room temperature for 36 hours to obtain a completed round floating point rubber coil, and then use a vulcanization tank to vulcanize the laminated coil, wherein the vulcanization temperature is 150°C and the vulcanization time is 20 minutes.

[0023] Further, the values ​​in steps S2 and S3 are changed, and steps S1 and S4-5 are performed, and the prepared wear-resistant, waterproof and anti-skid round floating point rubber coil is subjected to a performance test.

[0024] Embodiment 1: Step S2: Preparation of wear-resistant and non-slip surface layer 1: The pretreated natural rubber, silicone rubber, chloroprene rubber, filler, vulcanizer, accelerator, antioxidant and softener are put into an internal mixer according to the proportion, the internal mixing temperature is 100°C, the rotor speed is 60rpm, the mixing time is 10min, and the mixed rubber is obtained. The mixed rubber is then extruded by an extruder, and the mixed rubber is passed through a die with a round floating point shape to form a rubber sheet with a round floating point 4. The temperature of the extruder is 90°C, the screw speed is 25 rpm, then put the formed rubber sheet with round floating point 4 into a vulcanizing tank for vulcanization at a vulcanization temperature of 160°C for 15 minutes, and finally coat a layer of nano-silicon dioxide on one side with round floating point 4, and dry at a temperature of 50°C for 30 minutes to form a nano-silicon dioxide coating, wherein the mass ratio of natural rubber, silicone rubber, chloroprene rubber, filler, vulcanizing agent, accelerator, antioxidant and softener is 16:11:9:6:0.8:0.2:0.3:0.1; Step S3: Preparation of intermediate functional layer 2: The pretreated natural rubber and styrene-butadiene rubber are placed in an internal mixer for preliminary mixing, the mixing temperature is 80°C, the rotor speed is 30 rpm, and the mixing time is 7 min. Then, the rubber after preliminary mixing is rolled, and then the polyester fiber is added to the rubber, wherein the temperature is 90°C, the rotor speed is 50 rpm, and the mixing time is 8 min. Then, the vulcanizer and accelerator are added, and the mixing is continued at 90°C and 50 rpm for 4 min. Then, the mixed material is placed in a vulcanization device and vulcanized at 125°C for 25 min. The pretreated chloroprene rubber and a small piece of polyurethane foam were put into an internal mixer, and the mixture was rotated at 85°C and 40 rpm for 6 min. The vulcanizing agent, accelerator and antioxidant were added, and the mixture was continuously mixed at 85°C and 40 rpm for 4 min. The mixture was extruded to obtain a buffering performance layer 6, and the extruder temperature was 170°C. The asphalt was then placed in a high-speed mixer and preheated to 165°C. After the asphalt was melted, the SBS modifier was added and the mixture was heated to 130°C. The mixture was stirred at a high speed of 0 rpm, and after 40 minutes, talcum powder, antioxidant and stabilizer were added to the mixed system, and the stirring was continued at a speed of 1300 rpm for 40 minutes, wherein the temperature was maintained at 170°C, and the mixed material was extruded into a waterproof reinforcement layer 7, wherein the extruder temperature was 175°C, and finally, a rubber adhesive was applied to one side of the prepared enhanced physical performance layer 5, and then the prepared buffer performance layer 6 was laminated thereto, and a pressure of 0.7 MPa was applied using a platen press, and then a rubber adhesive was applied to the other side of the buffer performance layer 6, and the prepared The waterproof reinforcement layer 7 is bonded to it, and pressure is applied by a flat press, at this time the pressure is 1.5 MPa. After bonding, it is cured at room temperature for 36 hours to form a 2 mm intermediate functional layer 2, in which the mass ratio of natural rubber, styrene-butadiene rubber and polyester fiber, vulcanizer and accelerator is 7:3:0.6:0.1:0.2, the mass ratio of chloroprene rubber, polyurethane foam, vulcanizer, accelerator and antioxidant is 10:2:0.1:0.1:0.1, and the mass ratio of asphalt, SBS modifier, talcum powder, antioxidant and stabilizer is 10:0.4:0.2:0.1:0.1.

[0025] Furthermore, the tensile strength was measured to be 11.57MPa, the tear strength was 43.5kN / m, the Akron abrasion was 0.27cm³ / 1.61km, and in a dry environment: the static friction coefficient was 0.65, the dynamic friction coefficient was 0.58, in a wet environment, the static friction coefficient was 0.49, the dynamic friction coefficient was 0.36, the hydrostatic pressure was 0.31MPa, and the oxygen index was 24.8 Embodiment 2: Step S2: Preparation of wear-resistant and non-slip surface layer 1: The pretreated natural rubber, silicone rubber, chloroprene rubber, filler, vulcanizer, accelerator, antioxidant and softener are put into an internal mixer according to the proportion, the internal mixing temperature is 100°C, the rotor speed is 60rpm, the mixing time is 10min, and the mixed rubber is obtained. The mixed rubber is then extruded by an extruder, and the mixed rubber is passed through a die with a round floating point shape to form a rubber sheet with a round floating point 4. The temperature of the extruder is 90°C, the screw speed is 25 rpm, then put the formed rubber sheet with round floating point 4 into a vulcanizing tank for vulcanization at a vulcanization temperature of 160°C for 15 minutes, and finally coat a layer of nano-silicon dioxide on one side with round floating point 4, and dry at a temperature of 50°C for 30 minutes to form a nano-silicon dioxide coating, wherein the mass ratio of natural rubber, silicone rubber, chloroprene rubber, filler, vulcanizing agent, accelerator, antioxidant and softener is 20:11:9:6:0.8:0.2:0.3:0.1; Step S3: Preparation of intermediate functional layer 2: The pretreated natural rubber and styrene-butadiene rubber are placed in an internal mixer for preliminary mixing, the mixing temperature is 80°C, the rotor speed is 30 rpm, and the mixing time is 7 min. Then, the rubber after preliminary mixing is rolled, and then the polyester fiber is added to the rubber, wherein the temperature is 90°C, the rotor speed is 50 rpm, and the mixing time is 8 min. Then, the vulcanizing agent and accelerator are added, and the mixing is continued at 90°C and 50 rpm for 4 min. Then, the mixed material is placed in a vulcanization device and vulcanized at 125°C for 25 min. The pretreated chloroprene rubber and a small piece of polyurethane foam were put into an internal mixer, and the mixture was rotated at 40 rpm at 85°C for 6 min. The vulcanizing agent, accelerator and antioxidant were added, and the mixture was continuously mixed at 85°C and 40 rpm for 4 min. The mixture was extruded into an extruder to obtain a buffering performance layer 6, and the extruder temperature was 170°C. The asphalt was then placed in a high-speed mixer and preheated to 165°C. After the asphalt was melted, the SBS modifier was added and the mixture was stirred at 1300 °C. rpm for high-speed stirring, after 40 minutes, talcum powder, antioxidant and stabilizer are added to the mixed system, and stirring is continued at a speed of 1300 rpm for 40 minutes, wherein the temperature is maintained at 170°C, and the mixed material is extruded into a waterproof reinforcement layer 7, wherein the extruder temperature is 175°C, and finally, a rubber adhesive is applied to one side of the prepared enhanced physical performance layer 5, and then the prepared buffer performance layer 6 is laminated thereto, and a pressure of 0.7 MPa is applied using a platen press, and then a rubber adhesive is applied to the other side of the buffer performance layer 6, and the prepared waterproof The reinforcing layer 7 is bonded thereto, and pressure is applied thereto by a flat press, at this time the pressure is 1.5 MPa. After bonding, it is cured at room temperature for 36 hours to form a 2 mm intermediate functional layer 2, in which the mass ratio of natural rubber, styrene-butadiene rubber and polyester fiber, vulcanizer and accelerator is 7:3.5:0.6:0.1:0.2, the mass ratio of chloroprene rubber, polyurethane foam, vulcanizer, accelerator and antioxidant is 10:3:0.1:0.1:0.1, and the mass ratio of asphalt, SBS modifier, talcum powder, antioxidant and stabilizer is 12:0.4:0.2:0.1:0.1.

[0026] Furthermore, the tensile strength was measured to be 13.61 MPa, the tear strength was 46.3 kN / m, the Akron abrasion was 0.38 cm³ / 1.61 km, and in a dry environment: the static friction coefficient was 0.81, the dynamic friction coefficient was 0.63, in a humid environment, the static friction coefficient was 0.54, the dynamic friction coefficient was 0.48, the hydrostatic pressure was 0.42 MPa, and the oxygen index was 29.1.

[0027] Embodiment three: Step S2: Preparation of wear-resistant and non-slip surface layer 1: The pretreated natural rubber, silicone rubber, chloroprene rubber, filler, vulcanizer, accelerator, antioxidant and softener are put into an internal mixer according to the proportion, the internal mixing temperature is 100°C, the rotor speed is 60rpm, the mixing time is 10min, and the mixed rubber is obtained. The mixed rubber is then extruded by an extruder, and the mixed rubber is passed through a die with a round floating point shape to form a rubber sheet with a round floating point 4. The temperature of the extruder is 90°C, the screw speed is 25 rpm, then put the formed rubber sheet with round floating point 4 into a vulcanizing tank for vulcanization at a vulcanization temperature of 160°C for 15 minutes, and finally coat a layer of nano-silicon dioxide on one side with round floating point 4, and dry at 50°C for 30 minutes to form a nano-silicon dioxide coating, wherein the mass ratio of natural rubber, silicone rubber, chloroprene rubber, filler, vulcanizing agent, accelerator, antioxidant and softener is 22:12:9:6:0.8:0.2:0.3:0.1; Step S3: Preparation of intermediate functional layer 2: The pretreated natural rubber and styrene-butadiene rubber are placed in an internal mixer for preliminary mixing, the mixing temperature is 80°C, the rotor speed is 30 rpm, and the mixing time is 7 min. Then, the rubber after preliminary mixing is rolled, and then the polyester fiber is added to the rubber, wherein the temperature is 90°C, the rotor speed is 50 rpm, and the mixing time is 8 min. Then, the vulcanizing agent and accelerator are added, and the mixing is continued at 90°C and 50 rpm for 4 min. Then, the mixed material is placed in a vulcanization device and vulcanized at 125°C for 25 min. The pretreated chloroprene rubber and a small piece of polyurethane foam were put into an internal mixer, and the mixture was rotated at 40 rpm at 85°C for 6 min. The vulcanizing agent, accelerator and antioxidant were added, and the mixture was continuously mixed at 85°C and 40 rpm for 4 min. The mixture was extruded into an extruder to obtain a buffering performance layer 6, and the extruder temperature was 170°C. The asphalt was then placed in a high-speed mixer and preheated to 165°C. After the asphalt was melted, the SBS modifier was added and the mixture was stirred at 1300 °C. rpm for high-speed stirring, after 40 minutes, talcum powder, antioxidant and stabilizer are added to the mixed system, and stirring is continued at a speed of 1300 rpm for 40 minutes, wherein the temperature is maintained at 170°C, and the mixed material is extruded into a waterproof reinforcement layer 7, wherein the extruder temperature is 175°C, and finally, a rubber adhesive is applied to one side of the prepared enhanced physical performance layer 5, and then the prepared buffer performance layer 6 is laminated thereto, and a pressure of 0.7 MPa is applied using a platen press, and then a rubber adhesive is applied to the other side of the buffer performance layer 6, and the prepared waterproof The reinforcing layer 7 is bonded to it, and pressure is applied by a flat press, at this time the pressure is 1.5 MPa. After bonding, it is cured at room temperature for 36 hours to form a 2 mm intermediate functional layer 2, in which the mass ratio of natural rubber, styrene-butadiene rubber and polyester fiber, vulcanizer and accelerator is 7:3.5:0.8:0.1:0.2, the mass ratio of chloroprene rubber, polyurethane foam, vulcanizer, accelerator and antioxidant is 10:3:0.15:0.1:0.1, and the mass ratio of asphalt, SBS modifier, talcum powder, antioxidant and stabilizer is 13:0.5:0.2:0.1:0.1.

[0028] Furthermore, the tensile strength was measured to be 14.52MPa, the tear strength was 49.6kN / m, the Akron abrasion was 0.49cm³ / 1.61km, and in a dry environment: the static friction coefficient was 0.89, the dynamic friction coefficient was 0.69, in a humid environment, the static friction coefficient was 0.62, the dynamic friction coefficient was 0.57, the hydrostatic pressure was 0.49MPa, and the oxygen index was 34.7.

[0029] Embodiment 4: Step S2: Preparation of wear-resistant and non-slip surface layer 1: The pretreated natural rubber, silicone rubber, chloroprene rubber, filler, vulcanizer, accelerator, antioxidant and softener are put into an internal mixer according to the proportion, the internal mixing temperature is 100°C, the rotor speed is 60rpm, the mixing time is 10min, and the mixed rubber is obtained. The mixed rubber is then extruded by an extruder, and the mixed rubber is passed through a die with a round floating point shape to form a rubber sheet with a round floating point 4. The temperature of the extruder is 90°C, the screw speed is 25 rpm, then put the formed rubber sheet with round floating point 4 into a vulcanizing tank for vulcanization at a vulcanization temperature of 160°C for 15 minutes, and finally coat a layer of nano-silicon dioxide on one side with round floating point 4, and dry at a temperature of 50°C for 30 minutes to form a nano-silicon dioxide coating, wherein the mass ratio of natural rubber, silicone rubber, chloroprene rubber, filler, vulcanizing agent, accelerator, antioxidant and softener is 23:12:9:7:0.8:0.2:0.3:0.1; Step S3: Preparation of intermediate functional layer 2: The pretreated natural rubber and styrene-butadiene rubber are placed in an internal mixer for preliminary mixing, the mixing temperature is 80°C, the rotor speed is 30 rpm, and the mixing time is 7 min. Then, the rubber after preliminary mixing is rolled, and then the polyester fiber is added to the rubber, wherein the temperature is 90°C, the rotor speed is 50 rpm, and the mixing time is 8 min. Then, the vulcanizing agent and accelerator are added, and the mixing is continued at 90°C and 50 rpm for 4 min. Then, the mixed material is placed in a vulcanization device and vulcanized at 125°C for 25 min. The pretreated chloroprene rubber and a small piece of polyurethane foam were put into an internal mixer, and the mixture was rotated at 40 rpm at 85 ° C for 6 min. The vulcanizing agent, accelerator and antioxidant were added, and the mixture was continuously mixed at 85 ° C and 40 rpm for 4 min. The mixture was extruded to obtain a buffering performance layer 6, and the extruder temperature was 170 ° C. The asphalt was then placed in a high-speed mixer and preheated to 165 ° C. After the mixture was melted, an SBS modifier was added and the mixture was stirred at 1300 r. pm, and then talcum powder, antioxidant and stabilizer are added to the mixed system after 40 minutes, and the stirring is continued at a speed of 1300rpm for 40 minutes, wherein the temperature is maintained at 170°C, and the mixed material is formed into a waterproof reinforcement layer 7 through an extruder, wherein the extruder temperature is 175°C, and finally, a rubber adhesive is applied to one side of the prepared enhanced physical performance layer 5, and then the prepared buffer performance layer 6 is laminated thereto, and a pressure of 0.7MPa is applied using a platen press, and then a rubber adhesive is applied to the other side of the buffer performance layer 6, and the prepared waterproof reinforcement layer 7 is laminated thereto. Layer 7 is bonded thereto, and pressure is applied by a flat press at this time of 1.5 MPa. After bonding, it is cured at room temperature for 36 hours to form a 2 mm intermediate functional layer 2, in which the mass ratio of natural rubber, styrene-butadiene rubber and polyester fiber, vulcanizer and accelerator is 7:3.6:0.8:0.1:0.2, the mass ratio of chloroprene rubber, polyurethane foam, vulcanizer, accelerator and antioxidant is 10:3.5:0.15:0.1:0.1, and the mass ratio of asphalt, SBS modifier, talcum powder, antioxidant and stabilizer is 14:0.5:0.3:0.1:0.1.

[0030] Furthermore, the tensile strength was measured to be 14.18 MPa, the tear strength was 48.2 kN / m, the Akron abrasion was 0.41 cm³ / 1.61 km, and in a dry environment: the static friction coefficient was 0.88, the dynamic friction coefficient was 0.67, in a humid environment, the static friction coefficient was 0.61, the dynamic friction coefficient was 0.55, the hydrostatic pressure was 0.45 MPa, and the oxygen index was 33.5.

[0031] The performance test results of the wear-resistant, waterproof and non-slip round floating point rubber coil are as follows:

[0032] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A wear-resistant, waterproof and anti-skid round floating point rubber coil, characterized by: The invention comprises a wear-resistant and anti-skid surface layer (1), the bottom of the wear-resistant and anti-skid surface layer (1) is bonded with an intermediate functional layer (2), the bottom of the intermediate functional layer (2) is bonded with a base bonding layer (3), the top of the wear-resistant and anti-skid surface layer (1) is evenly arranged with round floating points (4), the round floating points (4) and the top of the wear-resistant and anti-skid surface layer (1) are coated with a 0.5 mm nano-silicon dioxide coating, the intermediate functional layer (2) comprises an enhanced physical performance layer (5), a buffer performance layer (6) and a waterproof reinforcement layer (7), the bottom of the waterproof reinforcement layer 7 is bonded with the top of the base bonding layer (3), the buffer performance layer (6) is located between the waterproof reinforcement layer (7) and the enhanced physical performance layer (5), and the top of the enhanced physical performance layer (5) is bonded with the bottom of the wear-resistant and anti-skid surface layer (1).

2. The wear-resistant, waterproof and anti-skid round floating point rubber coil according to claim 1, characterized in that: The raw materials include the following components: natural rubber, silicone rubber, chloroprene rubber, styrene-butadiene rubber, fillers, vulcanizers, accelerators, softeners, antioxidants, flame retardants, polyester fibers, polyurethane foams, stabilizers, talc, curing agents and diluents; The preparation method of the round floating point rubber coil comprises the following steps: Step S1: Raw material preparation and pretreatment: pretreating the natural rubber, silicone rubber and chloroprene rubber respectively; Step S2: firstly, preparing a wear-resistant and anti-skid surface layer (1), putting the natural rubber, silicone rubber and chloroprene rubber pretreated in step S1 into an internal mixer for mixing, and preparing a wear-resistant and anti-skid surface layer (1) with a thickness of 1.5 mm through an extrusion molding process; Step S3: Preparation of the intermediate functional layer (2): preparing the enhanced physical performance layer (5), the buffer performance layer (6) and the waterproof reinforcement layer (7), and using a bonding process to firmly combine the three-layer structure to form a 2 mm intermediate functional layer (2); Step S4: a polyurethane adhesive, a curing agent and a diluent are mixed in proportion, and stirred at a speed of 240-280 rpm for 10-20 minutes at room temperature to prepare an adhesive, and then the adhesive is evenly applied to one side of the intermediate functional layer (2) by a roller coater to form a 1 mm thick base adhesive layer (3), and a layer of release paper is covered on the other side of the base adhesive layer (3), wherein the mass ratio of the polyurethane adhesive, the curing agent and the diluent is 10:0.1-0.3:1-3; Step S5: Laminating and post-processing: Laminating the semi-finished product obtained in step S4 with the wear-resistant and anti-skid layer (1) to form a completed round floating point rubber coil, and vulcanizing the coil as a whole; Step S6: Quality monitoring and packaging: The physical properties of the manufactured coils are tested according to GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber" standard, and the flame retardant properties of the coils are tested according to GB10707-1989 "Rubber combustion performance determination oxygen index method".

3. The wear-resistant, waterproof and anti-skid round floating point rubber coil according to claim 2, characterized in that: In step S2, the following steps are also included: Step S21: putting the pretreated natural rubber, silicone rubber, chloroprene rubber, filler, vulcanizer, accelerator, antioxidant and softener into an internal mixer according to a certain proportion, with the internal mixing temperature being 90° C. to 110° C., the rotor speed being 50 to 70 rpm, and the mixing time being 5 to 10 min to obtain a mixed rubber; Step S22: Extruding the rubber mixture with an extruder and passing the rubber mixture through a die with round floating points to form a rubber sheet with round floating points (4), wherein the temperature of the extruder is 80°C to 90°C and the screw speed is 10 to 30 rpm; Step S23: placing the formed rubber sheet with round floating points (4) into a vulcanizing tank for vulcanization at a temperature of 150° C. to 170° C. for 10 to 20 minutes; Step S24: coating a layer of nano-silicon dioxide on the side with the round floating point (4), and drying at a temperature of 40-60° C. for 10-40 minutes to form a nano-silicon dioxide coating.

4. The wear-resistant, waterproof and anti-skid round floating point rubber coil according to claim 2, characterized in that: In step S1, the following steps are also included: Step S11: natural rubber pretreatment: natural rubber is put into an open mill, and nano calcium carbonate is added thereto, and the roller distance is adjusted to 1 mm, and the roller speed is 10-20 rpm for plastication for 5-8 minutes to obtain modified natural rubber; Step S12: silicone rubber pretreatment: firstly, the silicone rubber is placed in a plasma treatment device using plasma treatment technology, and activated for 2-3 minutes in an argon plasma atmosphere, and then the activated silicone rubber, AGE and chloroplatinic acid are placed in a reactor for a silylation reaction, so that the grafted monomer is grafted onto the silicone rubber molecular chain, wherein the temperature of the reactor is 85°C to 95°C, and the reaction time is 5 hours. After the reaction is completed, xylene is used for extraction to remove unreacted grafted monomer and catalyst, and the extracted silicone rubber is dried in a vacuum drying oven at a temperature of 85°C for 4.5 hours. Then, the grafted modified silicone rubber, flame retardant and zinc oxide are placed in an internal mixer at a temperature of 85°C to 95°C, a rotor speed of 40 to 60 rpm, and a mixing time of 5 to 10 minutes to obtain modified silicone rubber; Step S13: pretreatment of chloroprene rubber: put the chloroprene rubber into an internal mixer for preliminary mixing, the temperature of the internal mixer is 80°C to 85°C, the rotor speed is 30 to 50 rpm, after 4 to 6 minutes, add magnesium hydroxide and triphenyl phosphate, adjust the temperature to 90°C to 95°C, the rotor speed is 40 to 60 rpm, mix for 6 to 10 minutes, and obtain modified chloroprene rubber.

5. The wear-resistant, waterproof and anti-skid round floating point rubber coil according to claim 3, characterized in that: In step 3, the following steps are also included: Step S31: the pretreated natural rubber and styrene-butadiene rubber are placed in an internal mixer for preliminary mixing, the mixing temperature is 70°C to 90°C, the rotor speed is 30 to 40 rpm, and the mixing time is 5 to 10 min. Then, the rubber after preliminary mixing is rolled, and then polyester fiber is added to the rubber, wherein the temperature is 90°C, the rotor speed is 50-55 rpm, and the mixing time is 8-9 min. Then, a vulcanizing agent and an accelerator are added, and mixing is continued at 90°C and 50-55 rpm for 3-5 min. Then, the mixed material is placed in a vulcanizing device, vulcanized at 120-130°C for 25-30 min, and extruded by an extruder to obtain an enhanced physical property layer (5), wherein the extruder temperature is 160-170°C; Step S32: putting the pretreated chloroprene rubber and a small piece of polyurethane foam into an internal mixer, rotating at a temperature of 80-85° C. and a speed of 40-45 rpm, mixing for 5-8 minutes, then adding a vulcanizing agent, an accelerator and an antioxidant, continuing to internally mix at 80-85° C. and a speed of 40-45 rpm for 3-5 minutes, and extruding with an extruder to obtain a buffer performance layer (6), wherein the extruder temperature is 170° C.; Step S33: preheating the asphalt to 165°C in a high-speed mixer, adding SBS modifier after melting it, and stirring at a speed of 1200-1400 rpm. After 40 minutes, adding talcum powder, antioxidant and stabilizer into the mixed system, and stirring at a speed of 1200-1400 rpm for 40 minutes, wherein the temperature is maintained at 170°C, and the mixed material is extruded to form a waterproof reinforcement layer (7), wherein the extruder temperature is 175°C; Step S34: first, apply rubber adhesive to one side of the enhanced physical performance layer (5) prepared in step S31, and then laminate the buffering performance layer (6) prepared in step S32 thereon, and apply pressure of 0.5-1 MPa using a platen press, then apply rubber adhesive to the other side of the buffering performance layer (6), laminate the waterproof reinforcement layer (7) prepared in step S33 thereon, and also apply pressure of 1-2 MPa using a platen press. After lamination, cure at room temperature for 24-48 hours to form a 2 mm intermediate functional layer (2).

6. The wear-resistant, waterproof and anti-skid round floating point rubber coil according to claim 3, characterized in that: In step S5, the following steps are also included: Step S51: Laminating process: Apply adhesive to the other side of the middle functional layer (2), and then laminate the side of the wear-resistant and anti-skid layer (1) without the round floating point (4) thereto, and compact with a flat press at a pressure of 1-2 MPa. After laminating, leave it to stand at room temperature for 24-48 hours to obtain a completed round floating point rubber coil; Step S52: Overall vulcanization: Use a vulcanization tank to vulcanize the laminated coils, wherein the vulcanization temperature is 145-155° C. and the vulcanization time is 10-30 minutes.

7. The wear-resistant, waterproof and anti-skid round floating point rubber coiled material according to claim 2, characterized in that: In the step S21, the mass ratio of natural rubber, silicone rubber, chloroprene rubber, filler, vulcanizer, accelerator, antioxidant and softener is 15-25:10-13:9:5-10:0.5-1.5:0.1-0.5:0.3:0.

1.

8. The wear-resistant, waterproof and anti-skid round floating point rubber coil according to claim 4, characterized in that: The mass ratio of natural rubber to nano-calcium carbonate in step S11 is 10:0.1-0.5, and the mass ratio of chloroprene rubber, magnesium hydroxide and triphenyl phosphate in step S13 is 10:0.1-0.5:0.

2.

9. The wear-resistant, waterproof and anti-skid round floating point rubber coil according to claim 5, characterized in that: In the step S31, the mass ratio of natural rubber, styrene-butadiene rubber and polyester fiber, vulcanizer and accelerator is 7:3-4:0.5-1:0.1:0.2, in the step S32, the mass ratio of chloroprene rubber, polyurethane foam, vulcanizer, accelerator and antioxidant is 10:2-4:0.1-0.2:0.1:0.1, and in the step S33, the mass ratio of asphalt, SBS modifier, talcum powder, antioxidant and stabilizer is 10-15:0.3-1:0.1-0.5:0.1:0.

1.

10. The wear-resistant, waterproof and anti-skid round floating point rubber coil according to claim 4, characterized in that: In step S12, the flame retardant is a mixture of ammonium polyphosphate and melamine.

Citation Information

Patent Citations

  • Polymer rubber sports coiled material

    CN214194007U

  • Rubber composite self-adhesive waterproof coiled material

    CN219621120U